ABSORTÂNCIA SOLAR E AS NORMAS INTERNACIONAIS E BRASILEIRAS - Couto, Lorena; Banqueri, Daniela; Dornelles, Kelen (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The incidence of solar radiation on buildings envelope is considered one of the main responsible for its thermal load. Therefore, it is necessary to know the solar absorptance criteria of materials and coatings used on these surfaces in order to achieve better thermal performance. International researches and standards have shown that many countries, such as the United States, France, the United Kingdom, Italy, China and others, already adopt the criteria of solar absorptance or reflectance for the envelope surface materials, increasing the economy with high energy costs with AC systems. Brazilian standards have shown some delay in a substantial database for solar materials absorptance, although many studies are looking for better results.